Territorialisation et écologisation dans la filière forêt-bois française : une rencontre fortuite ? - Jonathan Lenglet; Sylvain Caurla (Développement Durable et Territoires)
This article explores the links between relocation and greening processes within the French forest-wood chain. We show that the parallel emergence of both processes led to the legitimization of the territory as a relevant scale for the implementation of ecological alternatives. The induced changes of the practices now make it clear that both processes should be considered as concomitant, operating at a key moment in the reorganization of the productive systems feeding on each other rather than being actually the cause or the consequence one of the other. While existing tools for the evaluation of practices are largely under development, a particularly fertile front is arising at the intersection of environmental and human sciences.